2021
DOI: 10.3390/ani12010056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in the Cardiac Function before and after Transcatheter Edge-to-Edge Mitral Valve Repair in Healthy Dogs: Conventional and Novel Echocardiography

Abstract: Mitral valve regurgitation is a common canine heart disease. Transcatheter Edge-to-Edge Repair (TEER) is a transcatheter, edge-to-edge mitral repair device that uses a hybrid approach. No detailed information has been published on the hemodynamic effect of TEER on cardiac function. The aim of this report is to provide a longitudinal observation of the cardiac functional changes observed after TEER implantation in normal dogs using traditional, two-dimensional speckle tracking, and color M-mode echocardiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In our study, there were some correlations between the CMME-derived indices and conventional echocardiographic parameters, particularly those that are important for diastolic function, as previously observed in other studies ( 7 , 9 12 , 16 , 37 ). The IVPD and IVPG indices reported in the present study were comparable to previous reports in dogs and cats ( 11 , 15 , 37 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, there were some correlations between the CMME-derived indices and conventional echocardiographic parameters, particularly those that are important for diastolic function, as previously observed in other studies ( 7 , 9 12 , 16 , 37 ). The IVPD and IVPG indices reported in the present study were comparable to previous reports in dogs and cats ( 11 , 15 , 37 ).…”
Section: Discussionsupporting
confidence: 89%
“…Since the PDA operation was performed via intercostal thoracotomy, neither catheterization nor angiography was performed for this study. A previous study showed that CMME-derived IVPD and IVPG were strongly correlated with tau measured by invasive catheterization, thus comparative assessment of IVPD between CMME and catheterization was not performed in this study ( 7 , 12 , 28 ). Besides, recent publications used CMME for non-invasive assessment of IVPD and/or IVPG that has been performed in dogs and cats without catheterization ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Myxomatous mitral valve disease (MMVD) resulting from degeneration of the valve leaflets and chordae tendineae is a common cardiac disorder causing congestive heart failure in dogs, especially in small breeds [1,2]. Surgical intervention for the advanced stages of canine MMVD is now available in some countries because of recent advances in surgical procedures [2][3][4][5]. In particular, mitral valvuloplasty (MVP) has been considered a treatment option for MMVD.…”
Section: Introductionmentioning
confidence: 99%